2011
DOI: 10.1590/s1807-59322011001200010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis virus infection in patients with multiple myeloma: clinical characteristics and outcomes

Abstract: OBJECTIVES:Cytotoxic agents and steroids are used to treat lymphoid malignancies, but these compounds may exacerbate chronic viral hepatitis. For patients with multiple myeloma, the impact of preexisting hepatitis virus infection is unclear. The aim of this study is to explore the characteristics and outcomes of myeloma patients with chronic hepatitis virus infection.METHODS:From 2003 to 2008, 155 myeloma patients were examined to determine their chronic hepatitis virus infection statuses using serologic tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 38 publications
(35 reference statements)
2
32
0
Order By: Relevance
“…Studies on the prevalence of blood-borne pathogen infections in different patients, such as those with chronic renal failure [18], myeloma patients [19], those with sickle cell diseases [41] and those with mental diseases [42] have been studied. To our knowledge, this is the first report to determine the infection status of four pathogens in eye patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the prevalence of blood-borne pathogen infections in different patients, such as those with chronic renal failure [18], myeloma patients [19], those with sickle cell diseases [41] and those with mental diseases [42] have been studied. To our knowledge, this is the first report to determine the infection status of four pathogens in eye patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an Indian study with 256 patients with chronic renal failure (138 had renal transplant and 118 were on maintenance haemodialysis), 7% were infected with HBV, 46% were infected with HCV [18]. The prevalence of HBV and HCV infection in 155 myeloma patients was reported as 11% and 9%, respectively, in Taiwan [19]. In general, the prevalence of infection is higher among hospitalised patients than in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The association between chronic HCV infection and lymphoproliferative diseases, including non‐Hodgkin's lymphoma (NHL), Hodgkin's lymphoma (HL) and MM, has been discussed for a long time. Several published studies showed a higher prevalence of HCV infection in MM than health control populations. A cohort study by Duberg et al .…”
Section: Introductionmentioning
confidence: 96%
“…Preemptive antiviral prophylaxis with nucleoside/nucleotide analogues should be considered in patients with latent or previous HBV infection. 68 Formal recommendation for those with a high risk of HCV infection or with previous infections are not available, but it seems reasonable to screen the high-risk group (anti-HCV and/or HCV RNA) and to treat those with evidence of active infection with modern direct-acting antivirals.…”
Section: Prophylaxis and Treatment Of Infectionsmentioning
confidence: 99%